Armament of Estonia: Arms Procurements of the Ministry of Defence in the 1990s - Nõmm, Toe (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2014)
An independent state must have its own army. If we don’t defend ourselves, someone else will come and defend us. The conflicts in the border areas of the collapsing Soviet Union and the Balkans in the 1990s as well as the unstable situation in Estonia and neighbouring countries underlined the need for the quick establishment of Estonia’s own army. At the time the state’s independence was restored, there were no people in Estonia who knew Western weaponry or how to carry out weapons procurements. The only things left behind by the Russian army were old gas masks, helmets, fuel and lubricants, a number of buildings and a polluted environment. The West did provide military assistance to Estonia from 1993–1996, but no weapons were given to us. Estonia received old equipment, uniforms and vehicles from Germany, Sweden, Finland, the US, Denmark and other countries, which also included things that had belonged to the liquidated East-German army. Estonia received a couple of L-410 jets, some helicopters and ships from the ‘bankruptcy estate’ of the latter. Hand guns, Kalashnikov rifles, ammunition etc. were bought from Romania and China. In 1993, Estonia managed to enter into a contract for purchasing weapons from the Israeli company IMI-TAAS. The defence budget comprised ca 4–5% of the state budget from 1993–2000. In 1996 the Estonian parliament set NATO membership as the state’s goal. Estonia participated actively in partnership programmes. From 1996/1997, Estonia finally started receiving aid with weapons from the West, which in addition to handguns included artillery guns, mortars, ships etc. This aid was important, as the state was poor. The first major procurements for weapons after the Israeli weapons deal were carried out at the start of the 21st century.